02.24 The ap-1 transcription factor c-jun promotes arthritis by regulating cyclooxygenase-2 expression in macrophages. (1st March 2017) - Hannemann, Nicole; Jordan, Jutta; Paul, Sushmita; Reid, Stephen; Baenkler, Hanns-Wolf; Sonnewald, Sophia; Bäuerle, Tobias; Vera, Julio; Schett, Georg; Bozec, Aline
Abstract : Background: Pro-inflammatory macrophage activation is associated with the inflammatory state of rheumatoid arthritis (RA). Their polarisation and activation are controlled by transcription factors, such as NF-κB and the AP-1 transcription factor members JunB or JunD. However, the role of the third JUN/AP-1 member, c-Jun, is still ill defined during macrophage activation in RA. Material and methods: To examine the role of c-Jun during macrophage activation, c-Jun deleted peritoneal macrophages were used for microarray and quantitative real-time PCR analysis. In addition, genes found differentially expressed were analysed by chromatin immunoprecipitation (ChIP) analysis to determine directs targets of c-Jun. To address the physiological role of c-Jun in macrophages, the serum induced arthritis (K/BxN) model was applied to c-Jun ΔLysM mice. Results: C-Jun mRNA and protein levels are increased in macrophages following pro- or anti-inflammatory stimulations. Gene Ontology (GO) and KEGG pathway enrichment cluster analyses of microarray data using wild-type and c-Jun deleted macrophages highlight the central function of c-Jun, in particular for immune response, interleukin production and hypoxia pathways. Mice deficient for c-Jun in macrophages showed an amelioration of inflammation and bone destruction in the K/BxN arthritis model. In vivo and in vitro gene profiling, together with ChIP analysis in macrophages unravelled direct activation of the pro-inflammatory factor cyclooxygenase-2 (Cox2) and indirect inhibition of the anti-inflammatory factor arginase-1 (Arg1) by c-Jun. Conclusion: Thus, c-Jun regulates the activation state of macrophages and promotes arthritis via differentially regulating Cox2 and Arg1 levels.